Learning perspectives on anxiety disorders - Eelen, Paul (2000)
From a moderate “nurture” standpoint, the authors propose the application of the psychology of learning to the theory and practice of anxiety disorders. The concepts of learning are analyzed through three learning paradigms: exposure to a stimulus, relationship between stimuli, and relationship between behavior and consequences. These paradigms are then related to anxiety. Based on preview and their own research, they defend an explanation of the origin and treatment grounded on a contemporary version of the associative viewpoint on anxiety disorders.